2006
DOI: 10.1007/s10554-006-9166-8
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of flow mediated vasodilatation of brachial artery in patients with primary hyperparathyroidism

Abstract: Endothelium-dependent FMD may impair in patients with PHPT compared to controls. Endothelial dysfunction can contribute to the deleterious cardiovascular effects of PTH excess. Therapy to reduce or retard endothelial dysfunction in patients with PHPT may lead to decreased cardiovascular morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 44 publications
3
26
0
1
Order By: Relevance
“…Flow-mediated dilatation (FMD) of brachial artery, a 'gold standard' of endothelial dysfunction also considered a surrogate marker of atherosclerosis, has been reported to be impaired in PHPT patients improving after PTx (24, 25). FMD has been shown to be negatively correlated with serum calcium levels (64). In contrast, some authors found no improvement in the FMD 3 years after PTx (26).…”
Section: Atherosclerosismentioning
confidence: 99%
“…Flow-mediated dilatation (FMD) of brachial artery, a 'gold standard' of endothelial dysfunction also considered a surrogate marker of atherosclerosis, has been reported to be impaired in PHPT patients improving after PTx (24, 25). FMD has been shown to be negatively correlated with serum calcium levels (64). In contrast, some authors found no improvement in the FMD 3 years after PTx (26).…”
Section: Atherosclerosismentioning
confidence: 99%
“…3,5,6 Few data are available with regard to large-artery properties in PH. Several studies have investigated endothelial dysfunction, 7,8 augmentation of peripheral pulse waveform 9,10 or the aortic stiffness index 11 in PH. So far, only one study has examined pulse wave velocity (PWV) as a measure of arterial stiffness in normotensive patients with PH.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is mainly due to cardiovascular death (2,3). PHPT is associated with hypertension, coronary heart disease, and other CVDs (7,15,17). There are only two studies to evaluate the hemostatic parameters in patients with PHPT (12,15).…”
Section: Discussionmentioning
confidence: 99%
“…The causes of increased cardiovascular risk associated with PHPT are systemic arterial hypertension (4), left ventricular hypertrophy (5), valvular and myocardial calcification (6), dysfunction in vascular reactivity (7,8), vascular structural changes (9), arrhythmias (10), impaired glucose metabolism (11,12), dyslipidemia (13), and increased body mass index (14). Very recently, changes in coagulation and fibrinolytic systems have been reported in patients PHPT, which might also have a role in the pathogenesis of cardiovascular disease (CVD) in this disease (12,15).…”
Section: Introductionmentioning
confidence: 99%